Agreement Between Instruments for Rating Treatment Decisional Capacity - Gurrera, Ronald J. (Am J Geriatr Psychiatry, 2007)
OBJECTIVE: The objective of this study was to measure agreement between three treatment decisional capacity assessment instruments in mild to moderate dementia. METHOD: Subjects (N = 79) were recruited from the community. Rating agreement was evaluated with kappa statistics. RESULTS: Three-way agreement was fair for overall capacity (κ = 0.451), very good for understanding (0.618), very poor for choice (0.158), and no better than chance for reasoning and appreciation. Pairwise agreement showed a similar pattern. CONCLUSIONS: With the exception of understanding, current treatment decisional capacity assessment instruments do not consistently agree with one another in assessing treatment decision abilities.